Utilization of low-concentration coal-bed gas to generate power using a core-shell catalyst-modified solid oxide fuel cell. (March 2020) - Yuan, Xiuqi; Chen, Huili; Tian, Wenjuan; Shi, Jing; Zhou, Wei; Cheng, Fangqin; Li, Si-Dian; Shao, Zongping
Abstract: This paper reports a way to utilize low-concentration coal-bed gas(LC-CBG) to generate power using SOFC technology. Ni–BaO–CeO2 @SiO2 (@NBC) porous nanoparticles with a core-shell structure were synthesized and applied as a protective layer on an anode consisting of Ni–yttria stabilized zirconia (Ni–YSZ). Catalytic activity of @NBC relative to methane partial oxidation was evaluated. Electrochemical performance and durability of the @NBC-modified cells (@NBC//Ni–YSZ) were tested fed with simulated LC-CBG (30% CH4 –70% air). A conventional cell without a protective layer (Ni–YSZ) and a bare NBC-modified cell (NBC//Ni–YSZ) were used for a comparison. The pre- and post-mortem microstructures of cells were analyzed. Influence of porosity of the anode layer on polarization resistance was also investigated. The loading mode of catalysts was discussed as well. Using simulated LC-CBG as a fuel, peak power density of @NBC//Ni–YSZ showed 50% increase at 800 °C comparing with Ni–YSZ at the same conditions. The aging test in galvano-static mode demonstrated good durability of @NBC//Ni–YSZ lasting for over 160 h when exposed to LC-CBG. For comparison, NBC//Ni–YSZ showed rapid voltage drop after 60 h. Voltage of the Ni–YSZ dropped after 10 h. No coking was observed on the @NBC//Ni–YSZ anode surface after the durability tests. Graphical abstract: NBC catalyst with a core-shell structure acts as an anodic catalytic layer of SOFC for LC-CBG fuel to generate power. Image 109 Highlights: Low concentration coal bed gas generates power using a solid oxide fuel cell. A Ni-based porous catalyst with a core-shell structure is synthesized. The catalyst-modified cell has good durability. The loading mode of anodic catalysts is discussed.